Ultrastructural changes in the ovary cells of engorged Rhipicephalus sanguineus female ticks treated with esters of ricinoleic acid from castor oil (Ricinus communis) - Sampieri, Bruno Rodrigues [UNESP]; Arnosti, Andre [UNESP]; Nunes, Pablo Henrique [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Chierice, Gilberto Orivaldo; Camargo Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2012)
Rhipicephalus sanguineus is a widely distributed tick species that has adapted to the urban environment, and the dog is its main host. This species is also known as a vector and reservoir of diseases caused by bacteria, protozoa, and viruses. Currently, acaricides of synthetic chemical origin have been widely and indiscriminately used, leading to the development of resistance to these products by ticks and causing damage to the environment. Thus, these issues have made it necessary to seek other forms of controlling these ectoparasites. R. sanguineus was artificially infested in host New Zealand White rabbits, which were divided into four treatment groups: control (CG1 and CG2) and treatment (TG1 and TG2) groups. TG1 and TG2 hosts were provided with feed supplemented with esters of ricinoleic acid from castor oil at a concentration of 5 g/kg of feed for 7 and 15 days. Afterward, the ovaries of the female ticks were removed for analysis by transmission electron microscopy. The results showed ultrastructural changes in the somatic and germ cells of ovaries from TG1 and TG2 females, particularly with respect to chorion deposition, a protective membrane of the oocyte, as well as in the transport process of vitellogenic materials via the hemolymph and pedicel cells. Moreover, the mitochondria were less electron-dense and had cristae that were more disorganized than the mitochondria from CG1 and CG2 individuals. Thus, this study demonstrated the action of esters on the ovaries of R. sanguineus, signaling the prospect of a way to control this ectoparasite without affecting nontarget organisms or the environment. Microsc. Res. Tech., 2012. (c) 2011 Wiley Periodicals, Inc.
Keywords: Rhipicephalus sanguineus; Ticks; Ultrastructure; Ricinoleic acid esters